Numerical Modeling of the Thermal Performance of Asphalt Solar Collector and Experimental Verification - العباس, فهد; هيثم حسن (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, an asphalt solar collector was numerically modeled using computational fluid dynamics (CFD) techniques and the validity of the simulated model was verified experimentally. In this research, circular-section metal pipes were used, wrapped in a U-shape, with a length of 3.42 m and placed inside an asphalt collector with a surface area of 0.52 . This collector was buried in the ground, where heat is transferred to the adjacent soil in order to match the real conditions. The experiment was conducted in Al-Mukharram region belonging to ​​Homs Governorate in the outdoor environment during the hot summer months, specifically on August 20 and 31. Water was passed through the collector pipes at a flow of 0.25 L/min, from 10:30 a.m. to 5 p.m. The results showed that The maximum thermal efficiency reached 69%, the maximum temperature difference is 12.63 0C, and the maximum hourly heat energy reached 800 kJ/h. The results also showed that the daily efficiency is not directly affected by the decrease in solar radiation in the last hours of the day, and this is considered an additional advantage for these collectors, which encourages the actual application of this technology within Syrian cities and for various areas of use. .